PEMENUHAN HAK-HAK PEKERJA WAKTU TERTENTU PADA MASA PANDEMI COVID-19 DI PT. MEDAN BIOENERGY NUSANTARA PEKANBARU - Krismo Apriyadi; Rika Lestari; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The main problem with Government Regulation Number 35 of 2021concerning Work Agreements for Specific Periods, Outsourcing, Working Timeand Break Time, and Termination of Employment is that through this regulation,severance pay for victims of layoffs is only half of the rule if a number ofconditions are met. One of them, severance half of the provisions if the companycloses and loses money.The type of research used is sociological juridical, namely researchconducted by identifying the law and how the effectiveness of the implementationof the law applies in society. Because in this study the authors directly conductedresearch at the location or place under study to provide a complete and cleardescription of the problem under study.The conclusions that can be obtained from the research results are First,the Fulfillment of Workers' Rights for a Certain Time During the Covid-19Pandemic Period in View of Government Regulation Number 35 of 2021Concerning Work Agreements for Specific Periods, Outsourcing, Working Timeand Rest Time, and Termination of Employment Relations (Study at PT. MedanBioenergy Nusantara) where workers/laborers basically get equality and theopportunity to get treatment without discrimination under any pretext to manifestthe welfare of workers and their families without neglecting profit and businesscompetition. Second, Obstacles to Fulfilling Workers' Rights for a Specific TimeDuring the Covid-19 Pandemic Period are reviewed from Government RegulationNumber 35 of 2021 Concerning Work Agreements for Specific Periods,Outsourcing, Working Time and Break Time, and Termination of Employment(Study at PT. Medan Bioenergy Nusantara), namely that there are not verydetailed regulations governing the fulfillment of workers' rights in a pandemicsituation, so that it is biased regarding the rights and obligations of businessactors and employees.Keywords: Fulfillment of Rights, Termination of Employment, Labor,Settlement.